2023
DOI: 10.1093/jrs/feac069
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Futures of International Refugee Law

Abstract: As refugee law practice enters the world of data, it is time to take stock as to what refugee law research can gain from technological developments. This article provides an outline for a computationally driven research agenda to tackle refugee status determination variations as a recalcitrant puzzle of refugee law. It first outlines how the growing field of computational law may be canvassed to conduct legal research in refugee studies at a greater empirical scale than traditional legal methods. It then turns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…21 To mitigate such harms, individuals and institutions must remain accountable and AI-based tools need to be explainable and grounded in an explicit normative framework. Organisations must be transparent about their use of AI and ensure that applicants are informed if algorithmic decision-making processes are applied to their data and Medicine, Science and the Law 64 (2) made aware of potential implications and ensure safeguards are in place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 To mitigate such harms, individuals and institutions must remain accountable and AI-based tools need to be explainable and grounded in an explicit normative framework. Organisations must be transparent about their use of AI and ensure that applicants are informed if algorithmic decision-making processes are applied to their data and Medicine, Science and the Law 64 (2) made aware of potential implications and ensure safeguards are in place.…”
Section: Discussionmentioning
confidence: 99%
“…This could assist with various stages of asylum processing, including information gathering, data sharing, planning, analysis and decision-making. 2,3 The AI streamlining of asylum casework through real-time language translation, potentially enables efficient communication between applicants and officials regardless of language barriers thus saving costs on translation services. Artificial Intelligence can assist in translating and organising vast quantities of documents, such as personal testimonies or legal paperwork, ensuring accuracy and consistency across multiple languages.…”
mentioning
confidence: 99%
“…Here, the authors used tabulation and the j 2 test to assess the statistical signicance of their ndings. In contrast with some of these prior ndings, Byrne et al [9] analysed a dataset of 15535 decisions from the Danish Refugee Appeals Board and found that the gender of the applicant and chairing judge, the applicant's marital status, and the age of the applicant are not signicantly associated with disparities in recognition rates, suggesting that some of these factors are more country specic. Beyond tabulation, researchers have used regression models in order to control for multiple factors.…”
Section: Asylum Adjudicationmentioning
confidence: 90%
“…However, as noted in [12] some applicant's characteristics might actually constitute legally relevant factors and are not necessarily problematic. Furthermore, as noted in [9] some prior ndings pertaining characteristics of the applicant or the decision maker do not necessarily extend beyond the jurisdictions in which they were found.…”
Section: Introductionmentioning
confidence: 93%
“…34 Within the Nordics, some of this work has been more akin to what Shaffer and Ginsburg have called an "empirical turn in international law", 35 an endeavour of typically US-based scholars more prone to employing quantitative methods and social science positivism as their preferred epistemology. As chronicled in another contribution to this special issue, computational analysis in particular has received growing attention in the Nordics as well, 36 and arguably as part of a more wide-spread application of quantitative methods.…”
Section: International Law and International Relations: Between A Roc...mentioning
confidence: 99%